Renal stone GWAS summary statistic files - Wiberg, A (University of Oxford, 2019)
UK Biobank GWAS (6,536 cases; 388,508 controls): SNP = marker ID, CHR = marker chromosome, BP = genomic position (hg19), ALLELE1 = effect allele, ALLELE0 = non-effect allele, A1FREQ = effect allele frequency, INFO = imputation score, BETA = beta, SE = standard error, P_BOLT_LMM_INF = association p-value.